(untitled) (Fiep Bulletin - online, 2011)
Sport and leisure are rights of all the Brazilians established by the Constitution of the Federal Republic of Brazil. Along with the warranty of rights the State’s duty obligatority is imposed by the establishment of public politics. It is intention of this paper to present preliminary results of the study about the public politics of sport and leisure of Curitiba, with administration of the Municipal Clerkship of Sport and Leisurre (SMEL). The impact that the public politics of sport and leisure provoke in the citizen was analysis object, having as specific objectives: the identification of the elements that compose the macrosystem and its influence in the human being development; the relationship and interdependence of the coercive factors in the citizen’s formation in the full exercise of their rights in the use of the leisure. The analysis was based on Bronfenbrenner’s Bio-ecological Model of the Human Development, composed by the nuclei: Process, Person, Context and Time. These acted as sustaining axis for analysis of the social context – Curitiba’s leisure’s public politics, identified as macrosystem, which embraces all the levels of contexts. For such, it was identified the user’s social-demographic profile (microsystem) of systematic corporal activities, its reasons and motives for the preferences, adhesion and permanence in SMEL’s sport and leisure programs. An interview structured along the sample with forty-two users identified in the systemic form the interference of the environment and its structures (mesosystem) and the processes that happen inside and among them. The relations and interconnections in the same environment even without the active participation of the person (exosystem) showed the interference in its development. The concern with health preservation and maintenance leads the citizen to count on the public politics revealing that they are devoted to the practice of corporal physical activities in their moments of leisure in detriment of the sporting practices and or of entertainment.